Natural Fibers from Vietnam Coffee Grounds as a Potential Reinforcement for Biocomposite Materials - Phan, Duong My Tien; Pham, Thanh Qui; Nguyen, Chi Thanh (Journal of Technical Education Science, 2024)
Coffee grounds were a common agricultural byproduct available in large quantities in many countries, containing a relatively high cellulose content of approximately 26.6–31.3%. Extracting cellulose fibers from coffee grounds was therefore both economically and environmentally significant. This study aimed to extract cellulose fibers from coffee grounds using a non-toxic and cost-efficient alkaline hydrogen peroxide extraction method. Scanning electron microscopy (SEM) analysis results indicated that, after being dried, the cellulose fibers tended to aggregate into bundles, with no individual fibers observed. The extraction yield was found to be 63.24%. Fourier transform infrared (FTIR) spectroscopy analysis revealed absorption peaks at wavenumbers corresponding to O-H, C-H, and C-O-C group vibrations, characteristic of the chemical structure of cellulose. The crystallinity index determined by X-ray diffraction (XRD) technique of the extracted cellulose fibers was 38.9%, higher than that of the raw coffee grounds. Thermogravimetric analysis (TGA) result indicated that the thermal stability of the obtained cellulose fibers was relatively lower than that of the coffee grounds. The obtained cellulose fibers have potential application as a reinforcing agent for biocomposite materials.